Além do cânon: mão invisível, ordem natural e instituições - Santos, Antonio Tiago Loureiro Araújo dos; Bianchi, Ana Maria (Estudos Econômicos (São Paulo), 2007)
The article proposes a non-canonical understanding of Adam Smith´s invisible hand, which implied a careful reading of the original texts and their framing in the historical and intelectual context of their time. To reach this goal, we identify the connection between the invisible hand and correlated notions (natural order, non-intentional consequences) and we discuss deism and the role of institutions in Smith´s thought. The discussion is preceded by a brief exposition of the behavioral foundations of the Smithian theory, in which we looked for a better support to our conclusions.